2014
DOI: 10.1021/ie502849w
|View full text |Cite
|
Sign up to set email alerts
|

DOSS Based QAILs: As Both Neat Lubricants and Lubricant Additives with Excellent Tribological Properties and Good Detergency

Abstract: DOSS − (dioctyl sulfosuccinate) based quaternary ammonium ionic liquids (QAILs) were synthesized and used as both neat lubricants and lubricant additives. The influence of structure on their miscibility, thermal stability, and tribological property was discussed. These QAILs are low cost as compared with conventional halogen-containing ionic liquids (ILs). They are noncorrosive and hydrolysis stable because of their halogen-free characteristics. The tribological properties of these QAILs as neat lubricants for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 36 publications
0
51
0
2
Order By: Relevance
“…Temperature is increased from ambient temperature to 600°C (10°C/min). The hydrolysis stability and the corrosion behavior of the [Ch][MA]ILs were assessed according to our previous work . Different samples were mixed with equal molar amount of water and then stirred at RT for a certain time.…”
Section: Methodsmentioning
confidence: 99%
“…Temperature is increased from ambient temperature to 600°C (10°C/min). The hydrolysis stability and the corrosion behavior of the [Ch][MA]ILs were assessed according to our previous work . Different samples were mixed with equal molar amount of water and then stirred at RT for a certain time.…”
Section: Methodsmentioning
confidence: 99%
“…Except for the polarity-induced surface absorption, under harsh sliding conditions, the active elements [N, F, P(B)] in ionic liquids offer sufficiently rich tribochemistry to form extreme pressure films of lower shearing strength by reacting with the fresh surface, which leads to lower friction coefficient and good wear resistance. It was found that ionic liquids as the additives in base oils also perform very well [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75]. The tribochemical reactions of ILs have been extensively studied.…”
Section: Ionic Liquids Additivesmentioning
confidence: 99%
“…Improved friction results were obtained when nonpolar base oils (mineral oils or polyalphaolefins) were used as main component in a binary mixture with polar compounds (esters or ionic liquids) [8,33,35,36,[58][59][60]. Mixtures of nonpolar base oil and an ester were also used in the preparation of an emulsion for lubricant purposes resulting in improved tribological behavior [61].…”
Section: Tribological Testsmentioning
confidence: 99%